Type I interferon in psoriasis: mechanisms and clinical implications - Chang Liu; Yidan Zhang; Xiaoqian Cui; Hailong Zhang; Jia Chen; Xiongwei Lian; Suqing Yang (Frontiers in Immunology, 2026)
Psoriasis is a chronic, recurrent, immune-mediated inflammatory skin disease in which the TNF/IL-23/IL-17 axis plays a central role in the maintenance of mature plaques. However, this classical framework does not fully explain the early immune events triggered by skin injury, barrier disruption, infection, and the release of self-nucleic acids. It also does not fully explain selected clinical phenotypes. Type I interferons (IFN-I) are inducible cytokines involved in antiviral defense and danger sensing that may shift from protective immune mediators to pathogenic inflammatory amplifiers in psoriasis-prone skin. Self-nucleic acids released after tissue injury can form immunostimulatory complexes with antimicrobial peptides such as LL37. These complexes activate innate immune responses and induce IFN-I production. This process can promote dendritic-cell maturation and amplify the IL-23/IL-17 inflammatory pathway. This review presents IFN-I as a stage-dependent and phenotype-specific immune module that links early danger sensing to subsequent inflammatory amplification in psoriasis. We focus on the protective role of IFN-I in skin danger responses, LL37-mediated abnormal nucleic acid sensing, multicellular IFN-I skin signatures, the stage-specific integration of IFN-I with the IL-23/IL-17 axis, and clinical contexts with increased IFN-I activity. Moreover, we briefly discuss the therapeutic significance of tyrosine kinase 2 as a convergence node for IL-23, IL-12, and IFN-I signaling. Defining the role of IFN-I across different lesion stages and clinical phenotypes may improve the immunopathological model of psoriasis. It may also provide a basis for disease stratification, response prediction, and individualized therapy.